2015
DOI: 10.18632/oncotarget.6493
|View full text |Cite
|
Sign up to set email alerts
|

Diet-derived 25-hydroxyvitamin D3 activates vitamin D receptor target gene expression and suppressesEGFRmutant non-small cell lung cancer growthin vitroandin vivo

Abstract: Epidemiologic studies implicate vitamin D status as a factor that influences growth of EGFR mutant lung cancers. However, laboratory based evidence of the biological effect of vitamin D in this disease is lacking. To fill this knowledge gap, we determined vitamin D receptor (VDR) expression in human lung tumors using a tissue microarray constructed of lung cancer cases from never-smokers (where EGFR gene mutations are prevalent). Nuclear VDR was detected in 19/19 EGFR mutant tumors. Expression tended to be hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 66 publications
1
34
0
Order By: Relevance
“…In vitro studies in breast cancer, colon cancer and lung cancer have shown that those cell lines that express VDR respond to VD supplementation with an anticarcinogenic effect. [22][23][24] Our study has some limitations. The small sample size of the study patients and the small number of patients with invasive, thick and metastatic MM might have influenced the lack of association between prognostic factors and VDR status, and no definite statements can be made in this subgroup of melanomas.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In vitro studies in breast cancer, colon cancer and lung cancer have shown that those cell lines that express VDR respond to VD supplementation with an anticarcinogenic effect. [22][23][24] Our study has some limitations. The small sample size of the study patients and the small number of patients with invasive, thick and metastatic MM might have influenced the lack of association between prognostic factors and VDR status, and no definite statements can be made in this subgroup of melanomas.…”
Section: Discussionmentioning
confidence: 94%
“…As in other neoplasms, tissue VDR status may suggest which patients with MM might be candidates for VD supplementation as an adjuvant treatment. In vitro studies in breast cancer, colon cancer and lung cancer have shown that those cell lines that express VDR respond to VD supplementation with an anticarcinogenic effect …”
Section: Discussionmentioning
confidence: 99%
“…148 Numerous studies have examined the ability of dietary or pharmacologic addition of vitamin D compounds to either prevent tumor formation or inhibit the growth of xenograft tumors. 82,[149][150][151][152][153][154][155][156][157][158][159] One area of investigation is the impact of experimental dietary variations and their impact on tumor predisposition. Long-term studies of mice fed with a Western-style diet (eg, high fat and phosphate and low vitamin D and calcium content) have been exploited to examine the impact of vitamin D on colon cancer proliferation.…”
Section: In Vivo Vitamin D Receptor Anticancer Actionsmentioning
confidence: 99%
“…Moreover, as a subgroup, they have been widely analyzed in multitudinous cancer-related studies [15,16]. However, in previously conducted studies, genetic variation in VDR has not been systematically analyzed with regard to NSCLC, and very limited data are available on CYP27B1 and CYP24A1 polymorphisms [17,18]. In addition, epidemiological and clinical studies inspecting the associations between NSCLC risk and vitamin D status are limited in number and inconclusive [19,20].…”
Section: Introductionmentioning
confidence: 99%